CREATIVITY & INNOVATION: IMPLICATIONS OF BUILDING CODES IN THE CITY OF GEORGETOWN, GUYANA - Yerianne Christa Haywood (Journal of Architecture&ENVIRONMENT, 2019)
Design Codes have been used as early as the Babylonian Era, where Hammurabi was responsible for some regulations which bore heavy constraints if they were broken. Design codes have since evolved over the years especially considering the experiences of major fires, natural disasters and also the advent of new materials and building techniques. These codes are estabished by private or governmental committees who are resposible for the develoment, maintenance and enforcement of these laws. Design codes also known as “building codes” have in some cases been viewed as major constraints on design creativity and innovation in architecture. This refers to the design problems that arise because of these rules and regulations. In the architectural community the need and importance of building codes is understood and accepted. However, some individuals are of the view that these regulations limit the potential of creativity and innovation in architectural design. Since they are too stringent and do not allow flexibility. While others are of the opinion that they give structure to design and pave the way for good design.This paper explores the nature of building codes, and creativity in the presence of these constraints. This paper mainly seeks to highlight the impacts of building codes on design creativity in the context of Guyana, South America. Guyana is a considered a developing country, as a case study, the paper focuses on the City of Georgetown, the capital city of Guyana. The results indicate that buildings codes can hinder creativity yet they are also needed for setting appropriate standards from design. Guyana has great potential for future development in the building construction industry, where the development of its building codes play an essential role for the creation and guidance of healthy principles of design.